Beneficiation of small South African coal using an air dense medium fluidized bed. Issue 5 (4th May 2022) - Diedericks, ES (Peters); Le Roux, M; Campbell, QP; Hughes, N
ABSTRACT: This paper investigates the air dense medium fluidized bed (ADMFB) as a suitable dry beneficiation technique to upgrade +5.6 mm-13.2 mm South African coal. The separation efficiency of the ADMFB was assessed by determining the effect, if any, of particle size range, medium to coal feed ratios, and the addition of vibration on the separation ability of the bed. The coal was upgraded to varying degrees, depending on the parameters of the applied methods. For example, when considering the bottom bed layer (one quarter of the total bed height) as discard, the cumulative ash yield of the clean coal fraction ranged between 13.0% and 17.6% with a corresponding yield of 82.21%–83.93%, respectively. A variation in feed coal PSD did not significantly influence the response of the bed pertaining to its ability to beneficiate the coal. This was quantified by the similarity in percentage ash yield for the feed, top and bottom layers. In addition, it was established that by feeding a coal and magnetite (+300 µm) mixture, in various mass ratios, did not significantly influence the separation efficiency of the bed, nor did the application of external vibration to the bed aid in the beneficiation of the coal. Although these factors did not influence the performance of the ADMFB, it was found that the minimum fluidization velocity and bed stability were largely improved by the introduction of these variables.